Error Analysis Elementary School Students in Mathematical Problem Solving Problems are Categorized Difficult UASBN - Sennen, Eliterius; Ndiung, Sabina; Supardi, Kanisius (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
This study attemps to describe and analyze the types of errors made byelementary school students in Manggarai Regency in solving mathematical problems in the difficultcategory, source of errors, and the affecting factors. The results of the study reveal that the types ofthestudents’ errors in solving mathematical problems categorized in UASBN were categorized into factualerrors, misconceptions, false belief, and poor skills. The source of the errors were dealt with misunderstandingof the question items, disconnection of concept, wrong mathematical models, inaccurate proceduresof completing the items, and unexact final results. Some factors contributing to these errors werelack of understanding, misconception, difficulty of finding the relationship of concepts, poor mastery ofproblem solving procedures, and inaccuracy or carelessness.Keywords: mathematics, students’ errors, difficult questions